Time-interval changes of cardiac cycles in fetal growth restriction. (August 2016) - Kurihara, Yasushi; Tachibana, Daisuke; Yokoi, Natsuko; Nakagawa, Kayoko; Kitada, Kohei; Hayashi, Masami; Yanai, Sakika; Katayama, Hiroko; Hamuro, Akihiro; Misugi, Takuya; Tanaka, Kazuharu; Fukui, Mitsuru; et al.
Abstract: Objective: The aims of this study were to investigate the time intervals of each component of cardiac flow velocity waveforms (FVWs) in fetuses with fetal growth restriction (FGR) and to compare these with those of normal fetuses using reference ranges. Methods: The durations of atrioventricular (AV) valve opening (AVVO), AV valve closure (AVVC), total E- (total-E) and A- (total-A) waves, total ejection time (total-ET), acceleration time (acc-E for E-wave, acc-A for A-wave, and acc-ET for ejection time), and deceleration time (dec-E for E-wave, dec-A for A-wave, and dec-ET for ejection time) were measured in fetuses with FGR. All variables were analyzed using z -scores. Results: Measurements of 17 growth-restricted fetuses were obtained. The time intervals between the last Doppler examination and delivery ranged from 0 to 6 days, with a median of 1 day. Significant increases were observed in AVVO, total-E, dec-E, and acc-A of the left heart. acc-E, acc-ET and AVVC of the left heart were significantly decreased. In the right heart, AVVO, total-E and dec-E were significantly increased. Conclusion: A prolonged time interval between early ventricular inflow and atrial contraction, as well as increased duration of AV valve opening, may reflect hemodynamic alterations in FGR fetuses.